A Comprehensive Multi-Omics Study of Serum Alterations in Red Deer Infected by the Liver Fluke Fascioloides magna - Josipa Kuleš; Miljenko Bujanić; Ivana Rubić; Karol Šimonji; Dean Konjević (Pathogens)
Liver fluke infections are acknowledged as diseases with global prevalence and significant implications for both veterinary and public health. The large American liver fluke, Fascioloides magna, is a significant non-native parasite introduced to Europe, threatening the survival of local wildlife populations. The aim of this study was to analyze differences in the serum proteome and metabolome between F. magna-infected and control red deer. Serum samples from red deer were collected immediately following regular hunting operations, including 10 samples with confirmed F. magna infection and 10 samples from healthy red deer. A proteomics analysis of the serum samples was performed using a tandem mass tag (TMT)-based quantitative approach, and a metabolomics analysis of the serum was performed using an untargeted mass spectrometry-based metabolomics approach. A knowledge-driven approach was applied to integrate omics data. Our findings demonstrated that infection with liver fluke was associated with changes in amino acid metabolism, energy metabolism, lipid metabolism, inflammatory host response, and related biochemical pathways. This study offers a comprehensive overview of the serum proteome and metabolome in response to F. magna infection in red deer, unveiling new potential targets for future research. The identification of proteins, metabolites, and related biological pathways enhances our understanding of host–parasite interactions and may improve current tools for more effective liver fluke control.